Targeting asparagine potentiates anti-PD-L1 immunotherapy in gastric cancer by enhancing CD8+ T cell anti-tumor response - Ge, Mingpai; Wang, Longfei; Zheng, Bowen; Zhan, Lu; Cui, Lu; Wang, Han; Huang, Enyuan; Xu, Yuan; Chang, Xusheng; Liu, Zhaorui; Xu, Jun; Yin, Kai (Frontiers in Immunology, 2025)
IntroductionImmunotherapy efficacy in gastric cancer (GC) is often constrained by the tumor microenvironment (TME), which is profoundly influenced by aberrant metabolism. Asparagine, an amino acid critical for neoplastic proliferation, also modulates CD8+ T cell metabolic programming. We investigated the impact of targeting asparagine on the GC immune microenvironment and its potential to synergize with anti-PD-L1 therapy.MethodsThe therapeutic efficacy of asparagine targeting was evaluated in GC tumor models. CD8+ T cell populations within the TME were analyzed by flow cytometry, while cytokine and chemokine levels (IFN-γ, GZMB, CXCL9, CXCL10) were quantified by ELISA. The effects on CD8+ T cell activation and antitumor function were assessed in vitro and in vivo. Synergistic efficacy with anti-PD-L1 therapy was evaluated in GC models, and the dependency on CD8+ T cells was confirmed via antibody-mediated depletion experiments.ResultsTargeting asparagine inhibited GC growth in vitro and in vivo, implicating immune system involvement. Mechanistically, asparagine targeting significantly increased the proportion of CD8+ T cells within the TME and upregulated the expression of IFN-γ, GZMB, CXCL9, and CXCL10. Furthermore, combining asparagine targeting with anti-PD-L1 therapy produced synergistic antitumor activity. This combined therapeutic effect was significantly attenuated by the depletion of CD8+ T cells.DiscussionOur findings indicate that targeting asparagine promotes CD8+ T cell activation and infiltration, thereby remodeling the GC immune microenvironment to enhance host antitumor immunity. The combination of asparagine targeting with anti-PD-L1 therapy elicits potent, synergistic antitumor effects that are demonstrably dependent on CD8+ T cells. This study provides a strong rationale for targeting asparagine metabolism as a novel strategy to improve immunotherapeutic outcomes in GC.